ANALISIS KESALAHAN SISWA BERDASARKAN TAHAPAN KASTOLAN DALAM MENYELESAIKAN SOAL MATERI BANGUN RUANG SISI DATAR PADA SISWA SMP KELAS VIII - Nabila Salsabila; Rippi Maya (IKIP Siliwangi, 2021)
The material for building a flat side is one of the important materials, because the material in it is related to everyday life. This study aims to analyze students' errors in solving questions about the material for building flat sides, based on the Kastolan stages. The research subjects were 30 students of class VIII SMPN 1 Tirtajaya, in Karawang. The technique for collecting data used was in the form of a written test of 5 description questions. Furthermore, from the test results, several student answers were selected to be analyzed for each error according to the Kastolan stage. Data analysis carried out is data reduction, data presentation and finally drawing conclusions. The results obtained that the students' work found conceptual errors, namely students did not know the formula to be used and did not match the completion steps because they did not read the questions carefully, procedural errors, namely students did not finish to completion, and technical errors, namely students were wrong in counting so that they produced answers. wrong. The conclusion that can be drawn from the results of this study is that students still experience many of these 3 types of errors to solve the problem of the description of the flat side space.